2011
DOI: 10.1007/978-3-7091-0661-7_23
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Associated Aneurysms with Arteriovenous Malformations of the Posterior Fossa

Abstract: The aim of this study was to determine the frequency of aneurysms associated with arteriovenous malformations (AVMs) of the posterior fossa and their relation to hemorrhagic presentation in comparison to supratentorial AVMs. We performed a retrospective analysis of 474 patients with intracranial AVMs treated in our center from 1990 to 2010. Patients were analyzed for AVM size, drainage type and their clinical course with focus on vessel anomalies including AVM-associated aneurysms. Seventeen (30%) of 57 poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Schmidt et al [10] reported a higher incidence of multiple AAs in infratentorial compared with supratentorial AVMs (41 vs. 26%), but did not comment on rupture rates, respectively. Thompson et al [17] could not confirm AA multiplicity to represent a potential risk factor for hemorrhage in both supra-and infratentorial AVMs.…”
Section: Impact Of Aa Multiplicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Schmidt et al [10] reported a higher incidence of multiple AAs in infratentorial compared with supratentorial AVMs (41 vs. 26%), but did not comment on rupture rates, respectively. Thompson et al [17] could not confirm AA multiplicity to represent a potential risk factor for hemorrhage in both supra-and infratentorial AVMs.…”
Section: Impact Of Aa Multiplicitymentioning
confidence: 99%
“…Bleeding from rupture of an AA was only assumed when meeting the previously defined criteria by Schmidt et al [10] and confirmed by angiographic morphological or intraoperative findings ( fig. 1 ).…”
Section: Clinical Presentation and Definition Of Aneurysm Rupturementioning
confidence: 99%
See 1 more Smart Citation
“…Associated aneurysms were the source of bleeding in 10.5% of cases of infratentorial AVMs but only 1.7% of cases of supratentorial AVMs. 8 In the series of posterior fossa AVMs reported by da Costa et al,…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Some authors have previously noticed that prenidal aneurysm ruptures were frequent when AVMs were located in the posterior fossa. 2,8,12 We sought to confirm, in a series of cases involving patients with AVMs who were treated at our institution, that patients with posterior fossa AVMs frequently present with hemorrhage associated with prenidal aneurysm ruptures. We also aimed to review the outcome for patients presenting with such ruptures who were treated by endovascular means.…”
mentioning
confidence: 99%